Analysis Of Humanitarian Discourse In Mahmoud Abbas’ Speech At The 2018 UN Session: A Fairclough Perspective: Taḥlīl al-Khiṭāb al-Insānī fī Khiṭāb Maḥmūd ‘Abbās fī Jalsat al-Umam al-Muttaḥidah li ‘Ām 2018: Manẓūr Fairclough - Ahsan Rasyid, Muhammad; Salbiah, Rahma (An-Nahdah Al-'Arabiyah, 2025)
This research aims to decipher the talk of humankind displayed in Palestinian President Mahmoud Abbas's discourse within the 73rd Joined together Countries (UN) Common Gathering of 2018. Palestinian freedom from the Israelian occupation could be an exceptionally complex universal matter since numerous variables avoid the goal. The strategy that will be utilized in this inquire about could be a subjective strategy with an expressive approach The Critical Discourse Analysis (CDA) hypothesis of Norman Fairclough. The result of this ponder is the talk of humankind found in Mahmoud Abbas's discourse that has awakened to such phonetic components as lexicon and sentence. Such components lead to an extraordinary talk which is additionally impacted by such intertextual perspectives as social and cultural. Concurring to Fairclough's hypothesis, the structure of a talk comes about from an outside figure of dialect building a literary development because it did with Mahmoud Abbas's discourse content. The developing universal bolster and part of the Joined together Country (UN) as a world peace organization proceeds to campaign the compassionate talk of Palestine autonomy has given the Palestinian President's opportunity to bring Palestinian desires and desires through the 73rd UN common get together of 2018. يهدف هذا البحث إلى كشف الخطاب الإنساني الذي ظهر في خطاب الرئيس الفلسطيني محمود عباس خلال الدورة الثالثة والسبعين للجمعية العامة للأمم المتحدة عام 2018. إن استقلال فلسطين عن الاحتلال الإسرائيلي قضية دولية معقدة للغاية بسبب العديد من العوامل التي تعيق تحقيقها. تعتمد هذه الدراسة على منهج نوعي باستخدام مقاربة وصفية تستند إلى نظرية التحليل النقدي للخطاب (CDA) لنورمان فيركلاف. أظهرت نتائج هذه الدراسة أن الخطاب الإنساني في خطاب محمود عباس يتجلى في عناصر لغوية مثل المعجم وبنية الجملة. تشكل هذه العناصر خطابًا قويًا يتأثر أيضًا بالجوانب التناصية مثل العوامل الاجتماعية والثقافية. ووفقًا لنظرية فيركلاف، فإن بنية الخطاب تتشكل من العوامل الخارجية للغة التي تبني التكوين النصي، كما هو الحال في محتوى خطاب محمود عباس. إن الدعم الدولي المتزايد والدور الذي تلعبه الأمم المتحدة كمنظمة عالمية للسلام يواصلان الترويج للخطاب الإنساني بشأن استقلال فلسطين، مما منح الرئيس الفلسطيني فرصة لعرض تطلعات وآمال الشعب الفلسطيني من خلال الدورة الثالثة والسبعين للجمعية العامة للأمم المتحدة عام 2018. Penelitian ini bertujuan untuk mengungkap wacana kemanusiaan yang ditampilkan dalam pidato Presiden Palestina, Mahmoud Abbas, pada Sidang Umum Perserikatan Bangsa-Bangsa (PBB) ke-73 tahun 2018. Kemerdekaan Palestina dari pendudukan Israel merupakan permasalahan internasional yang sangat kompleks karena banyak faktor yang menghambat penyelesaiannya. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan deskriptif berdasarkan teori Analisis Wacana Kritis (Critical Discourse Analysis/CDA) dari Norman Fairclough. Hasil dari penelitian ini menunjukkan bahwa wacana kemanusiaan dalam pidato Mahmoud Abbas tercermin dalam unsur-unsur linguistik seperti leksikon dan struktur kalimat. Unsur-unsur ini membentuk wacana yang kuat, yang juga dipengaruhi oleh aspek intertekstualitas, termasuk faktor sosial dan budaya. Menurut teori Fairclough, struktur suatu wacana terbentuk dari faktor eksternal bahasa yang membangun konstruksi tekstual, sebagaimana terjadi dalam isi pidato Mahmoud Abbas. Dukungan internasional yang terus berkembang serta peran Perserikatan Bangsa-Bangsa (PBB) sebagai organisasi perdamaian dunia terus mengkampanyekan wacana kemanusiaan dalam perjuangan kemerdekaan Palestina. Hal ini memberikan kesempatan bagi Presiden Palestina untuk menyampaikan harapan dan aspirasi rakyat Palestina melalui Sidang Umum PBB ke-73 tahun 2018.